Latest Findings in Intellectual and Developmental Disabilities Research - Tan, ner (IntechOpen, 2012)
Intellectual and Developmental Disabilities presents reports on a wide range of areas in the field of neurological and intellectual disability, including habitual human quadrupedal locomotion with associated cognitive disabilities, Fragile X syndrome, autism spectrum disorders, Down syndrome, and intellectual developmental disability among children in an African setting. Studies are presented from researchers around the world, looking at aspects as wide-ranging as the genetics behind the conditions to new and innovative therapeutic approaches.